Early versus late rapid force production during single-joint isometric hamstring assessment using force plates - Ripley, N. J.; Barber, R.; Fahey, J. T.; Comfort, P. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to assess differences in time-matched early versus late rapid force (RF) development in female soccer players in the 90-90 isometric hamstring assessment. Twenty-one elite female soccer players (age: 20.7 ± 4.7 years; height: 168.2 ± 5.5 cm; body mass: 62.8 ± 7.0 kg), with no recent (>6 months) history of hamstring strain injury, volunteered to participate in the study. Following a standardized warm-up, each subject performed 3 maximal isometric unilateral hamstring contractions, with their heel resting on a force plate, elevated on a box, to ensure that their hips and knees were at 90°. Data were analyzed to determine peak force, early RF (ERF) 0-100 milliseconds and late RF (LRF) 100-200 milliseconds. Significant and large differences were observed in the percentage of peak force achieved between ERF (52.85 ± 11.53%; 54.99 ± 9.80%) and LRF (15.82 ± 5.58%; 15.25 ± 3.91%) for the left and right limbs, respectively (p < 0.001, g = 2.13-3.06). The large differences between ERF and LRF can be used by practitioners to streamline performance assessment, which in turn will allow practitioners to act upon data collected more effectively. Additionally, regular monitoring ERF production could inform practitioners of any interventions that maybe required, such as reduction of load or introduction of specific recovery modalities and during return to play protocols.